2006
DOI: 10.1053/j.gastro.2006.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Glial-Derived Neurotrophic Factor Modulates Enteric Neuronal Survival and Proliferation Through Neuropeptide Y

Abstract: Background and Aims-Glial Derived Neurotrophic factor (GDNF) promotes the survival and proliferation of enteric neurons. Neuropeptide Y (NPY) is an important peptide regulating gastrointestinal motility. The role of NPY on the survival and proliferation of enteric neurons is not known. We examined the effects of GDNF on the expression and release of NPY from enteric neurons and the role of NPY in promoting enteric neuronal proliferation and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 56 publications
4
53
0
Order By: Relevance
“…Moreover, NPY also stimulates the proliferation of neuronal progenitor cells (BrdU + /nestin + cells), which means that NPY promotes the proliferation of committed neural immature cells. Other studies also showed that NPY promotes proliferation of neuroblasts of olfactory epithelium, hippocampal precursor cells and rat enteric neurons (Hansel et al 2001;Howell et al 2003Howell et al , 2005Howell et al , 2007Anitha et al 2006). Using pharmacological tools, we also demonstrate that NPY increases cell proliferation through the activation of NPY Y 1 , Y 2 and Y 5 receptors.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, NPY also stimulates the proliferation of neuronal progenitor cells (BrdU + /nestin + cells), which means that NPY promotes the proliferation of committed neural immature cells. Other studies also showed that NPY promotes proliferation of neuroblasts of olfactory epithelium, hippocampal precursor cells and rat enteric neurons (Hansel et al 2001;Howell et al 2003Howell et al , 2005Howell et al , 2007Anitha et al 2006). Using pharmacological tools, we also demonstrate that NPY increases cell proliferation through the activation of NPY Y 1 , Y 2 and Y 5 receptors.…”
Section: Discussionsupporting
confidence: 76%
“…The NPY receptor subtypes involved in the proliferative effect induced by NPY in other cell types is a matter of controversy. Most studies suggest that the NPY Y 1 receptor is mainly involved (Hansel et al 2001;Howell et al 2003Howell et al , 2005Howell et al , 2007Cho and Kim 2004;Milenkovic et al 2004;Anitha et al 2006). However, in vascular smooth muscle cells and endothelial cells some reports demonstrate that the mitogenic effect of NPY is mediated by Y 1 , Y 2 and Y 5 receptors (Zukowska-Grojec et al 1998;Lee et al 2003;Kitlinska et al 2005;Movafagh et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDNF has been shown to increase NPY expressing neurons. One of the possible mechanisms GDNF could influence β-cell mass could be through NPY 13 . Future studies will examine this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was assessed either by Western blotting for cleaved caspase-3 or cleaved caspase-3 with immunofluorescence microscopy 12,13 .…”
Section: Apoptosismentioning
confidence: 99%